More-than-human Perspectives on Physical Activity, Health and Education - Bortolotti, Alessandro; Fullagar, Simone; Mora, Bruno; Shuilleabhain, Niamh Ni; Ugolotti, Nicola De Martini; Bueno, Alessandra Xavier; Donato, Antonio; Galak, Eduardo; Tonelli, Leonardo (2022)
The Culture/Nature dualism has supplied post-Enlightenment philosophers, scientists and social scientists with a neat way to set limits on the respective concerns of the social and natural sciences (see Barad, 2007; Braidotti, 2013; Fullagar et al., 2019), and has enabled the creation of distinctions between "modern" (read "civilised") and "traditional" (read "primitive") bodies and ways of being-in-the-world (Denowski and Viveiros de Castro, 2014). Yet, when critically exploring issues of embodiment, the influence of the built environment on well-being, climate transitions and/or the ongoing Covid-19 pandemic such distinctions start to become problematic, as eloquently argued in the last three decades by feminist, post-human, new-materialist and political ecological -among others- debates and propositions. Giving continuity to an ongoing dialogue started in 2018 between scholars and activists from Latin America and Europe (see Donato, Tonelli, Galak, 2019) this seminar explored how the interrelated domains of health, physical activity, and education can look like from perspectives that de-stabilise established ontological boundaries between nature, culture, the body, and their relationship. It did so through a dialogue between Alessandro Bortolotti, Simone Fullagar, Bruno Mora, Niamh Ni Shuilleabhain, four scholars from Australia, Italy, United Kingdom and Uruguay. The online event took place as the first of a two-parts online seminar series on Re-assembling the nature-culture-body nexus: practices and epistemologies.
Keywords: Education; Health; Physical activities; New materialism; More-than-human perspectives